Mxi1-0 Promotes Hypoxic Pulmonary Hypertension Via ERK/c-Myc-dependent Proliferation of Arterial Smooth Muscle Cells - Dong, Liang; Liu, Xinning; Wu, Bo; Li, Chengwei; Wei, Xiaomin; Wumaier, Gulinuer; Zhang, Xiujuan; Wang, Jing; Xia, Jingwen; Zhang, Yuanyuan; Yiminniyaze, Ruzetuoheti; Zhu, Ning; et al. (Frontiers in Genetics, 2022)
Background: Hypoxic pulmonary hypertension (HPH) is a challenging lung arterial disorder with remarkably high incidence and mortality, and so far patients have failed to benefit from therapeutics clinically available. Max interacting protein 1-0 (Mxi1-0) is one of the functional isoforms of Mxi1. Although it also binds to Max, Mxi1-0, unlike other Mxi1 isoforms, it cannot bind to Max or antagonize the oncoprotein c-Myc because of its unique proline rich domain (PRD). While Mxi1-0 was reported to promote cell proliferation via largely uncharacterized mechanisms, it is unknown whether and how it plays a role in the pathogenesis of HPH. Methods: GEO database was used to screen for genes involved in HPH development, and the candidate players were validated through examination of gene expression in clinical HPH specimens. The effect of candidate gene knockdown or overexpression on cultured pulmonary arterial cells, e.g. pulmonary arterial smooth muscle cells (PASMCs), was then investigated. The signal pathway(s) underlying the regulatory role of the candidate gene in HPH pathogenesis was probed, and the outcome of targeting the aforementioned signaling was evaluated using an HPH rat model. Results: Mxi1 was significantly upregulated in the PASMCs of HPH patients. As the main effector isoform responding to hypoxia, Mxi1-0 functions in HPH to promote PASMCs proliferation. Mechanistically, Mxi1-0 improved the expression of the proto-oncogene c-Myc via activation of the MEK/ERK pathway. Consistently, both a MEK inhibitor, PD98059, and a c-Myc inhibitor, 10058F4, could counteract Mxi1-0-induced PASMCs proliferation. In addition, targeting the MEK/ERK signaling significantly suppressed the development of HPH in rats. Conclusion: Mxi1-0 potentiates HPH pathogenesis through MEK/ERK/c-Myc -mediated proliferation of PASMCs, suggesting its applicability in targeted treatment and prognostic assessment of clinical HPH.